Strategi Komunikasi Badan Usaha Milik Desa Bartong Dalam Meningkatkan Motivasi dan Partisipasi Masyarakat Melalui Sadar Wisata - Nur, Tengku Azizah (Universitas Muhammadiyah Sumatera Utara, 2025)
Tourism in Indonesia continues to grow rapidly, encouraging the development of tourist villages as an effort to improve the economy and community welfare. Bartong Village, which has the potential for Bahbolon River tourism, faces the challenge of low tourism awareness and community participation in tourism management. BUMDes has an important role in increasing community motivation and participation in tourism management. This study focuses on how the communication strategy of BUMDes Bartong in increasing community motivation and participation through tourism awareness. The method used in this study is descriptive qualitative. The data collection techniques for this study are observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. This study uses the Kulvisaechana theory which consists of frequency, level of formality, message content, and channels. The location of the study was in Bartong Village, Sipispis District, Serdang Bedagai Regency, North Sumatra. This study was conducted from November 2024 to March 2025. The results of this study indicate that the communication carried out by BUMDes Bartong in increasing community tourism awareness is quite effective and running well, but there is still room for improvement, especially in increasing the frequency and success of communication with the community. With more consistency and more diverse methods, community participation in supporting sustainable tourism management can continue to increase.Tourism in Indonesia continues to grow rapidly, encouraging the development of tourist villages as an effort to improve the economy and community welfare. Bartong Village, which has the potential for Bahbolon River tourism, faces the challenge of low tourism awareness and community participation in tourism management. BUMDes has an important role in increasing community motivation and participation in tourism management. This study focuses on how the communication strategy of BUMDes Bartong in increasing community motivation and participation through tourism awareness. The method used in this study is descriptive qualitative. The data collection techniques for this study are observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. This study uses the Kulvisaechana theory which consists of frequency, level of formality, message content, and channels. The location of the study was in Bartong Village, Sipispis District, Serdang Bedagai Regency, North Sumatra. This study was conducted from November 2024 to March 2025. The results of this study indicate that the communication carried out by BUMDes Bartong in increasing community tourism awareness is quite effective and running well, but there is still room for improvement, especially in increasing the frequency and success of communication with the community. With more consistency and more diverse methods, community participation in supporting sustainable tourism management can continue to increase.